Cytotoxic effects of paclitaxel-loaded hyaluronic acid nanoparticle on selected cancer cell lines - Chaudhry, Gul E Saba; Md. Akim, Abdah; Abdullah, Mohd Azmuddin (Penerbit Universiti Malaysia Terengganu, 2016)
Cancers are among the major leading cause of death globally. In the cancer clinical management strategies, chemotherapy in combination with radiotherapy, show more promising results. However, there are issues related to drug adverse side effects, and the drug candidates not deliverable through the preferred route or in some cases, at all, owing to poor water solubility. There is a special need to improve drug solubility and to facilitate its intravenous administration for effective targeting to cancerous cells, with enhanced therapeutic efficiency and sustained/control release properties. In this study, Paclitaxel (PTX)-entrapped HA nanoparticles (NPs) were synthesized to determine the cytotoxicity on lung (A549), breast (MCF-7) and colorectal (HT-29) cancer cell lines. HA-PTX showed promising cytotoxic effects on all the three cell lines with 2-3 fold increase as compared to PTX alone. Drug release study showed that PTX was released in a biphasic manner. An increase in ADP/ATP ratio and caspase 8 in all cancer cell lines, the hallmark of apoptosis (Programmed Cell Death), suggests that HA-PTX had induced apoptosis. The increase in caspase 8 activation may suggest the involvement of extrinsic pathway apoptosis in cancer cell lines. This suggested that HA-PTX has the potential as candidate in the overall drug therapeutic strategies with enhanced cytotoxicity on cancer cell lines.